A civil action - Rudin, Scott; Redford, Robert; Pfeffer, Rachel; Zaillian, Steven; Touchstone Pictures; Paramount Pictures; Scott Rudin Productions; Touchstone Home Video (firm); Buena Vista Home Entertainment (firm) ([United States] : Touchstone Home Video : distributed by Buena Vista Home Entertainment, 1999)
The families of children who died sue two companies for dumping toxic waste. A tort so expensive to prove that the lawyer were almost bankrupt in the process
Based on the book by Jonathan Harr
Music by Danny Elfman ; director of photography, Conrad L. Hall; edited by Wayne Wahrman
Cast : John Travolta, Robert Duvall, Tony Shalhoub, William H. Macy, Zeljko Ivanek, Bruce Norris, John Lithgow, Kathleen Quinlan
Keywords: Trials (Toxic torts) -- Massachusetts -- Boston -- Drama; Groudwater -- Pollution -- La and legislation -- Massachusetts -- Woburn -- Drama; Drinking water -- Contamination -- Massachusetts -- Woburn -- Drama; Liability for water pollution damages -- Massachusetts -- Woburn -- Drama